Epidemiological, Clinical, And Occupational Characteristics of Migrant Workers Confirmed with COVID-19 At Udayana University Hospital - Paramita, Ni Putu Pradnya; Wirawan, I Made Ady; Purnamasidhi, Cokorda Agung Wahyu; Florensia, Maria; Akatsu, Haruko (Institute of Topical Disease Universitas Airlangga, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has prompted Indonesian expatriates to return home. Travel history, including migrant repatriation, was thought to spread COVID-19. These factors increased COVID-19 transmission. This study examined the epidemiological, clinical, and occupational characteristics of migrant workers with COVID-19 at Udayana University Hospital. This descriptive study utilized a cross-sectional methodology. The research samples consisted of 97 migrant workers diagnosed with COVID-19 who had been treated at Udayana University Hospital between March to August of 2020, using the total sampling technique. The median age (IQR) of migrant workers is 30, and 84.53% are male. Before returning to Indonesia, many worked and visited the US (20.6%). 87.63% of respondents worked in hospitality sector, and mostly worked in 8–12-hour shifts. All respondents have insurance; most employers are provided with PPE and information regarding COVID-19 prevention. At the airport, COVID-19 screening revealed fever (70.6%) and cough (76.3%) as the most common symptoms. A 94.8% of migrant workers had no comorbidities, and 87.6% had normal chest X-rays. From this research, we discovered that amongst migrant workers, positive-COVID-19 results were mostly found in young, mobile men. Most of them worked for 8–12 hours per day, and majority worked in hospitality sector. Almost all of them did not have any comorbidities and the most common symptoms found were fever and cough. The findings suggest that male workers in their productive age with high mobility and working in the hospitality sector are at higher risk of infection.